ANALISIS EFEKTIVITAS PENGGUNAAN MODAL KERJA PADA PT. FRESMON PACIFIK PRIMA DI SAMARINDA - Rachmawati, Endah (EKONOMIA, 2013)
The purpose of this paper is to analyze the effectiveness of the use of working capital in PT. Fresmon Pacific Prima in Samarinda, in 2009 until 2012.For the purposes of this paper, the main issues raised "Is the use of working capital in PT. Prima in Samarinda Fresmon Pacific from 2009 to 2012 has been effective? "Based on these basic problems, it proposed the following hypothesis: "The use of working capital in PT. Prima in Samarinda Fresmon Pacific from 2009 to 2012 have been effective ".Analysis tools used in this study is to calculate the ratio likuidas, profitability and working capital turnover with the data analysis is the comparison of Balance Sheet and Income Statement ranging from 2009 to 2012.After going through the stages of research, analysis and discussion in mind that the ability of the company to meet all obligations finansisal short term (liquidity) and a company's ability to generate profits or earnings (earnings) can be said to be decreased or did not improve from the previous year or have not been effective. While the calculation of working capital turnover company also showed a decrease or not effective.Thus the hypothesis that the use of working capital in PT. Pacific Fresmon Prima has not been proven effective or hypothesis is rejected.